Electroporation-based therapies for cancer : from basics to clinical applications - Sundararajan, R. (Woodhead Publishing series in biomedicine, 2014)
Electroporation-Based Therapies for Cancer reviews electroporation-based clinical studies in hospitals for various cancer treatments, including melanomas, head and neck cancers, chest wall breast carcinomas, and colorectal cancers, as well as research studies in the lab using cell lines, primary cells, and animals. Cancer kills about one American per minute, amounting to over 500,000 deaths in the United States and millions, worldwide, each year. There is a critical need for safe, effective, and affordable alternative treatment modalities, especially for inoperable, recurring, and chemo-resistant cancers, that do not respond well to current treatment regimen.